2021
DOI: 10.1037/pas0001022
|View full text |Cite
|
Sign up to set email alerts
|

Item response theory analysis of the Triarchic Psychopathy Measure.

Abstract: This study investigated item and scale functioning in the triarchic psychopathy measure (TriPM) using an item response theory (IRT) analysis. TriPM data collected from 937 (410 men and 527 women) college students and community members were analyzed. A graded response model was utilized to analyze the items comprising the TriPM's three scales. Exploratory factor analyses (EFAs) supported the unidimensionality of the Disinhibition and Meanness scales, whereas Boldness was best represented by two domains. Each Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Sample 2 (Eichenbaum et al, 2021) included college students and North American community members recruited through MTurk. These data were collected for an item response theory study of the Triarchic Psychopathy Measure (TriPM; Patrick et al, 2009).…”
Section: Sample 2: Mturk and Sonamentioning
confidence: 99%
“…Sample 2 (Eichenbaum et al, 2021) included college students and North American community members recruited through MTurk. These data were collected for an item response theory study of the Triarchic Psychopathy Measure (TriPM; Patrick et al, 2009).…”
Section: Sample 2: Mturk and Sonamentioning
confidence: 99%
“…This finding was consistent with a previous IRT study finding that reverse-scored items are usually uninformative when scored in the opposite direction as the majority of the other items in the scale (Eichenbaum et al, 2019). Although reverse-scored items can be applied to reduce socially desirable responding, it was suggested that the psychometric cost might outweigh these advantages (Eichenbaum et al, 2021). The face validity of the items is also questionable from a phenomenological perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The same study further supported full SI. In the study by Eichenbaum et al (2021), 61% of the TriPM items (n = 34) displayed DIF. Women scored lower than men on all three factors in the study by Carre et al (2018;boldness, t (474) = 5.874, p < 0.001; meanness, t (474) = 8.262, p < 0.001, and disinhibition, t (474) = 3.898, p < 0.001).…”
Section: Tripmmentioning
confidence: 95%